A patient-centered approach can improve rational drug use. A cross-sectional study - Kocoglu, Mirac; Yakar, Burkay; Onalan, Erhan (Termedia Publishing House Ltd, 2024)
Background. The current study aimed to investigate the rational drug use characteristics of physicians and the effect of a patient -centered approach on rational drug use. Material and methods. This cross-sectional and descriptive study was conducted with 182 assistant doctors from November 2020 to April 2021 in a university hospital. Rational drug use features are evaluated by World Health Organization (WHO) prescribing indicators. The patient -centered approach of physicians was measured by the Patent -Practitioner Orientation Scale (PPOS-14). Results. The mean number of drugs per prescription in the study was 3.0 +/- 1.03. 66.5% of the doctors reported that they prescribed drugs to more than half of their patients. Physicians with high patient -centered approach scores were more likely to call their patients by their names, use more from drug guides, follow their patients' treatment processes, and showed interest in interest in rational drug use studies, and rational drug use training. Physicians who prefer ready -to -use prescriptions for common conditions had lower patient -centered approach scores. There was a significant positive correlation between the PPOS-14 total score and the rational drug use score ( r = 0.153, p = 0.039), and there was a significant negative correlation between PPSO share and care scores and the average number of drugs per prescription. Conclusions. Physicians with a patient -centered approach were more willing to use rational drugs, follow rational drug guidelines, and receive training on rational drug use. Bringing the patient -centered approach to physicians may improve rational drug use.
Keywords: drug prescriptions; World Health Organization; patient-centered care